A Taxonomy for selecting global supply chain strategies. - Christopher, Martin; Peck, Helen; Towill, Denis R. (MCB UP Ltd/Emerald Group Publishing Limited, 2006)
This paper addresses the increasingly important question of supply chain design for global operations. With the rise of off-shore sourcing and the simultaneous need for improved responsiveness to customer demand, the choice of supply chain strategy is critical.
Keywords: Agile production; Lean production; Sourcing; Supply chain management